EFEKTIVITAS MODEL PEMBELAJARAN PJBL DENGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN BERPIKIR REFLEKTIF SISWA MATERI BAGIAN TUMBUHAN - Ratna Ningsih, Elok; Rosmiati; Ladyawati, Erlin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of implementing the Project-Based Learning (PjBL) model with a Deep Learning approach on improving students reflective thinking skills on the topic of plant parts in fourth-grade elementary school students. Science education (IPA) at the elementary school level requires an approach that not only focuses on understanding scientific concepts but also on developing reflective thinking skills. This ability enables students to connect the knowledge they have gained with everyday experiences, analyze information, and develop solutions to problems they encounter. Based on initial observations, it was found that students' reflective thinking skills on the topic of plant parts were still low, which serves as the key reason for conducting this research. This study employs a descriptive quantitative approach, conducted at SDN Keboananom Gedangan, Sidoarjo, involving two experimental groups of fourth-grade students. Data were collected through pretests and posttests to measure changes in students' reflective thinking skills, as well as surveys to assess students responses to the teaching model applied. Pretests were conducted before the teaching model was implemented, and posttests were conducted after the model was applied to evaluate improvements in students' reflective thinking skills. The results show that the implementation of the PjBL model with a Deep Learning approach has a positive impact on improving students' reflective thinking skills. Project-based learning allows students to become more actively engaged in the learning process, think critically, and connect the knowledge they have gained to their real-life experiences. Students were given the opportunity to observe, record, and analyze data related to the topic of plant parts, which encouraged them to think deeply and reflectively. In addition, students were able to see the connection between the theory they learned and its application in daily life.